1948
DOI: 10.1017/s0022172400036573
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic disease of newborn foals due to iso-immunization of pregnancy

Abstract: 1. Six cases of haemolytic disease in newborn foals apparently due to iso-immunization of pregnancy are described from their clinical, serological, haematological and pathological aspects. The findings agree closely with those seen in the same disease in newborn mules.2. The disease may be diagnosed serologically by demonstrating the in vivo iso-sensitization of the foal's red cells by means of the direct antiglobulin-sensitization test. It is quite possible that after further investigation a modification of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1949
1949
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…При цьому досліджується велика кількість чинників, які можуть впливати на основні показники спер-мограм жеребців: гормональний фон, порода, вік, пора року, загальний фізіологічний стан, мікотоксини, загальна хромосомна нестабіль-ність та інші [5][6][7][8][9][10]. Водночас асоційований зв'язок алелів еритроцитарних антигенів із показниками свіжеотриманих еякулятів пра-ктично не вивчається, незважаючи на те, що ще в 40-х роках ХХ століття було доведено їх кореляційний вплив на фертильний потенціал коней [11]. Якщо у людини сьогодні офіційно визнано 29 систем груп крові з 35 існуючих [12], то у коней відомо лише 9 подібних систем, у тому числі найбільше практичне значення мають лише 4 з них: А, С, D, К, зв'язок яких з показниками спермограм не досліджували; у фізіології коней вивчали лише особливості антигенного профілю ери-троцитів при збільшенні кількості абортів та при появі гемолітичної хвороби лошат після їх народження [4,6,11].…”
Section: вступunclassified
“…При цьому досліджується велика кількість чинників, які можуть впливати на основні показники спер-мограм жеребців: гормональний фон, порода, вік, пора року, загальний фізіологічний стан, мікотоксини, загальна хромосомна нестабіль-ність та інші [5][6][7][8][9][10]. Водночас асоційований зв'язок алелів еритроцитарних антигенів із показниками свіжеотриманих еякулятів пра-ктично не вивчається, незважаючи на те, що ще в 40-х роках ХХ століття було доведено їх кореляційний вплив на фертильний потенціал коней [11]. Якщо у людини сьогодні офіційно визнано 29 систем груп крові з 35 існуючих [12], то у коней відомо лише 9 подібних систем, у тому числі найбільше практичне значення мають лише 4 з них: А, С, D, К, зв'язок яких з показниками спермограм не досліджували; у фізіології коней вивчали лише особливості антигенного профілю ери-троцитів при збільшенні кількості абортів та при появі гемолітичної хвороби лошат після їх народження [4,6,11].…”
Section: вступunclassified
“…This does not seem to be only a matter of the height of the titre of antibody in the maternal serum, as is shown by a comparison (see Table 1) of the titres found in doe F, whose offspring could have had sensitized red cells but in fact did not, with the titres found in an animal such as doe A or doe D, whose offspring had sensitized cells. An important point we must establish, before further discussion on this question is possible, is to which of the systems of rabbit red cell antigens our antisera relate, for it has been shown by Fischer (1935) (Coombs et al 1948) it was found that antibodies in the sera of thoroughbred mares, whose foals showed haemolytic anaemia with in vivo sensitization of their red cells, were demonstrated also by the appropriate indirect sensitization test, though again often only at the higher dilutions of the serum. These findings can only be noted now, and cannot be discussed without further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-CorneU Medical Center, New York (Received for publication, August 8, 1952) Naturally occurring erythroblastosis retails has been observed in man and in certain strains of horses (1,2) and donkeys (3), while some features of the disease have also been produced experimentally in dogs (4) and pigs (5). There are, however, a number of important differences between the disease as it occurs in man and that found naturally or induced experimentally in animals.…”
Section: (From the Department Of Pathology And The Central Laboratorimentioning
confidence: 99%
“…In the first place, only the hemolytic aspects of the disease have been reported in animals; hydrops fetalis, intrauterine death, kemicterns, and other serious manifestations of the disease have thus far been observed only in man. Furthermore, in erythroblastosis fetalis in human beings the antibodies responsible for the disease cross the placenta from mother to fetus and affect the fetus in utero; whereas in the horse, donkey, dog, and pig the offending antibodies are not acquired from the mother during intrauterine life but during the first few hours after birth from the colostmm or milk (1)(2)(3)(4)(5). In addition, in the experimentally induced disease of dogs and pigs immunization does not take place incidentally to pregnancy, as it does in human beings, but occurs only following the injection into the female of erythrocytes containing specific blood group factors absent from her red cells.…”
Section: (From the Department Of Pathology And The Central Laboratorimentioning
confidence: 99%